Multilayers fast mode decision algorithms for scalable video coding - Gunawan, Teddy Surya; Maarif, Haris Al Qodri; Khalifa, Othman Omran (INSI Publications, 2011)

(untitled)
Scalable video coding (SVC) is the extension of H.264/AVC standard. The features in SVC are also developed from the H.264/AVC standard, so that SVC has more features compared to H.264/AVC standard. This provides higher coding complexity in SVC encoder which causes higher encoding time for SVC. SVC is gaining great interest because of its ability and scalability to adapt in various network conditions. SVC allows partial transmission and decoding of a bitstream. This research deals with multilayers fast mode decision algorithm for decreasing encoding time or fastening the mode decision process of the SVC encoder. The proposed fast mode decision scheme has been implemented and is successfully decrease encoding time with negligible loss of quality and bitrate requirement. The simulation result shows the proposed fast mode decision algorithm provides time saving up to 45 % while maintaining video quality with negligible PSNR loss.